2001
DOI: 10.1677/joe.0.1680409
|View full text |Cite
|
Sign up to set email alerts
|

Mid-luteal angiogenesis and function in the primate is dependent on vascular endothelial growth factor

Abstract: Vascular endothelial growth factor (VEGF) is essential for the angiogenesis required for the formation of the corpus luteum; however, its role in ongoing luteal angiogenesis and in the maintenance of the established vascular network is unknown. The aim of this study was to determine whether VEGF inhibition could intervene in ongoing luteal angiogenesis using immunoneutralisation of VEGF starting in the mid-luteal phase. In addition, the effects on endothelial cell survival and the recruitment of periendothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Inhibition of LH signalling using GNRH antagonists mimicked this effect, also suppressing early luteal angiogenesis and implicating the LH surge in normal luteal angiogenesis, consistent with the described induction of VEGFA signalling by LH (Koos 1995, Dickson & Fraser 2000. The in vivo inhibition of VEGFA signalling throughout the luteal phase (days 3-10 in the marmoset monkey) also decreased luteal angiogenesis and the blood concentration of progesterone (Dickson et al 2001, Wulff et al 2001c. Recently, a study carried out by Christensen et al (2012) indicated that treatment with progesterone increased the levels of VEGFA, KDR and angiopoietin 1 (ANGPT1 (ANG1)) in the CL of anoestrous ewes.…”
Section: Discussionsupporting
confidence: 71%
“…Inhibition of LH signalling using GNRH antagonists mimicked this effect, also suppressing early luteal angiogenesis and implicating the LH surge in normal luteal angiogenesis, consistent with the described induction of VEGFA signalling by LH (Koos 1995, Dickson & Fraser 2000. The in vivo inhibition of VEGFA signalling throughout the luteal phase (days 3-10 in the marmoset monkey) also decreased luteal angiogenesis and the blood concentration of progesterone (Dickson et al 2001, Wulff et al 2001c. Recently, a study carried out by Christensen et al (2012) indicated that treatment with progesterone increased the levels of VEGFA, KDR and angiopoietin 1 (ANGPT1 (ANG1)) in the CL of anoestrous ewes.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, endothelial cells may be particularly sensitive to the loss of growth factor support during tubule initiation. A requirement for positive survival signals in luteal development has been suggested (Hojo et al 2010) and apoptotic endothelial cells have been localised in primate corpora lutea following VEGFA-suppression (Dickson et al 2001). In addition, the FGF2-independence that develops over time in culture in this study may reflect an increasing resistance to endothelial cell apoptosis that occurs as vessel-like structures mature and recruit perivascular cells (Benjamin et al 1998(Benjamin et al , 1999.…”
Section: Fgf2 and Luteal Endothelial Cell Sproutingmentioning
confidence: 66%
“…However, endothelial cells are also among the first cells to undergo apoptosis, or "angioregression" during regression of the CL [8]. There is general agreement that a surge of angiogenesis occurs within the CL during its initial development, which is characterized by increased proliferation of endothelial cells and secretion of vascular endothelial cell growth factor (VEGF), and the upregulation of angiopoetins [9][10][11][12][13][14][15]. There is discrepancy, however, about whether or not a second surge of angiogenesis occurs during early pregnancy [9,11,13,16].…”
mentioning
confidence: 99%